The misalignment of real effective exchange rate: Evidence from Tunisia - Ahmed Derbali (Graduate Institute of International and Development Studies, 2021)
This paper presents an estimation of the Tunisian equilibrium exchange rate based on the Behavioral Equilibrium Exchange Rate approach (BEER). The BEER framework links exchange rates to its fundamentals: Tunisian productivity, partners' productivity, trade openness and terms of trade. We calculate the distortion between the observed Real Exchange Rate (RER) and the equilibrium rate, and the misalignments related thereto. Vector autoregressive models and vector error correction models are applied to characterize the joint dynamics of variables in the long run, using quarterly data over the period 1990-2020.We find that this period was marked by phases of overvaluation and undervaluation of the RER. The empirical results indicate a low sensitivity of the RER to monetary and trade shocks. Indeed, the error correction mechanism on the one hand confirms one of the convergences of the real exchange rate series of its trajectory to its long-term target value. On the other hand, it reflects the success of monetary and commercial policies exploited to absorb unpredictable shocks capable of preventing the stability of real exchange rate from its equilibrium value.
Keywords: C32; F31; O55; 330; Equilibrium exchange rate; Misalignment; BEER approach; Error correction model